دراسة تحليلية لواقع الأمن الغذائي في سورية خلال الفترة 2006-2010 - جحجاح محسن سليم; صقر ابراهيم حمدان; اسماعيل ريم ابراهيم (Latakia University Journal -Biological Sciences Series, 2013)
يهدف هذا البحث إلى التعرف على واقع الأمن الغذائي في سورية خلال الفترة 2010-2006، إذ تبين أن مجموعة الحبوب تشكل أهم الزراعات في سورية، حيث تشغل 64.18% من مساحة الأراضي المزروعة، ويشكل القمح أهم مكوناتها، إذ كانت نسبة نمو إنتاجه2.24% خلال الفترة 2000-2010، وهي أكبر من مثيلاتها في العالم والوطن العربي. حققت سورية الاكتفاء الذاتي الكامل في القمح119.4%، البطاطا110.5%، البقوليات168%، الفواكه102.7%، الخضر146.9% وغيرها، أما بالنسبة لمتوسط نصيب الفرد في سورية من الحبوب فقد بلغ 345.16 كغ، وهو أكبر من مثيله في الوطن العربي بمقدار 36.17 كغ وعند حساب قيمة الفجوة الغذائية في سورية، فتبين انها زادت من 42.5 مليون دولار عام 2006، إلى 1412.23 مليون دولار عام 2010, وذلك بسبب ارتفاع قيمة الفجوة الغذائية لمجموعة الحبوب التي بلغت 976.32 مليون دولار، وهي تشكل 47.17% من قيمة سلة العجز الغذائي عام 2010. وبالنسبة لمؤشرات الحصول على الغذاء في سورية، فقد كانت إيجابية، إذ زاد الرقم القياسي لمتوسط نصيب الفرد من الناتج المحلي عن الرقم القياسي لأسعار المواد الغذائية، بشكل واضح، أعوام 2007-2008-2010، كما أن معدل النمو الحقيقي لنصيب الفرد من الناتج المحلي كان موجباً عام 2006 ،إذ بلغ 9.18 %، ولكنه نقص إلى %3.7 عام 2010. This research aims to identify the reality of food security in Syria between the years 2006- 2010. The most important crops in Syria are grain crops, occupying 64.18% of the area of ​​cultivated land. Wheat is the most important grain; it had production growth rate of 2.24% between the years 2000- 2010. This is higher than wheat production growth rate not only in the Arab world but in the whole world. This production rate allowed Syria to achieve self-sufficiency in wheat 119.4%, potatoes 110.5%, legumes 168%, fruits 102.7, vegetables 146.9%, in addition to other products. The average per capita in Syria is 345.16 kg of grain per person which is greater than that in the Arab world by 36.17 kg. The value of food gap in Syria increased from 42.5 million dollars in 2006 to 1412.23 million dollars in 2010. This was due to the increase of grain food gap which reached 976.32 million dollars. It was still, however, within reasonable limits. The indicators of access to food in Syria were positive as the index of average individual share of local production per capita was higher than the index of food prices in 2007, 2008, and 2010. The true growth of individual share of local products per capita was positive in 2006 reaching 9.18%, but it shrank to 3.7% in 2010.